Bacteriological study of post-operative wound infections with special reference to MRSA and ESBL in a tertiary care hospital - Rajput, Rashmi Basavantsing; Telkar, Anjana; Chaudhary, Ansh; Chaudhary, Bhupendra (International Journal of Advances in Medicine, 2019)
Background: Surgical site infections are known to be one of the most common causes of nosocomial infections worldwide and raises an important public health concern. Methods: A prospective observational study was conducted across 12 months (July 2018-June 2019) in a tertiary care hospital. The present study includes 50 pus samples from clinically suspected cases of post-operative wound infections from various surgical wards which were inoculated in Department of Microbiology. The phenotypic identification of different bacterial isolates especially MRSA and ESBL producers along with their antimicrobial susceptibility testing was interpreted according to CLSI guidelines. Results: Out of 50 samples, 44 showed positive culture. The infections were more common in emergency situations, age group of 20-30 years and in females. The most common bacterial isolates were Staphylococcus aureus (43.18%) followed by E. coli (22.72%), Klebsiella (15.9%), CONS (13.63%) and Pseudomonas (4.54%). Out of 19 Staphylococcus aureus 9 were MRSA and these gram-positive bacteria were highly sensitive to Linejolid and Clindamycin. In gram negative group 22.72% of E. coli and 15.9% of Klebsiella were ESBL producers who were susceptible mainly to Aztreonam, Linezolid or Cefoxitine. Conclusions: Post-operative wound or surgical site infections is the most important factor responsible for significant morbidity, mortality, prolonged hospitalization and additional cost to treatment in surgical patients. Marked resistance of isolates to commonly used antibiotics indicates the need of judicious use of these drugs to prevent the emergence of multi-drug resistant strains.